Fiscal Multipliers and Institutions in Peru : Getting the Largest Bang for the Sol - Vtyurina, Svetlana (IMF Working Papers; Working Paper, 2016)
With the end of the commodity super cycle, Peru's potential growth has declined, raising questions of what government policies could do to help boost growth, including over the medium-term. Our econometric analysis shows that public investment multipliers have a larger effect on growth than current spending or tax-related stimulus in the short and medium terms. Peru's low debt and financial savings grants fiscal space for increasing investment spending, which could also entice and complement private investment, provided the former is efficient, fiscally sustainable and complemented by further reforms in public investment management and changes to the decentralization framework.